2021
DOI: 10.2147/cmar.s318378
|View full text |Cite
|
Sign up to set email alerts
|

SP1-Regulated Non-Coding RNA SNHG22 Promotes Ovarian Cancer Growth and Glycolysis

Abstract: Objectives Long non-coding RNAs (lncRNAs) play a crucial part in cancer progression. However, in epithelial ovarian carcinoma (EOC), the role of SNHG22 needs to be further explained. Methods Quantitative real-time PCR was used to detect the expression of SNHG22. EOC cells were stably transfected with lentivirus approach and cell proliferation, glycolysis and cell apoptosis, as well as tumorigenesis in animal were performed to assess the effects of SNHG22 in EOC. Chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…34,35 Furthermore, transcription factors SP1 and PU.1 have been admittedly confirmed to directly bind to glycolytic gene promoters and induce the transcription of key glycolytic enzymes to promote glycolysis. [36][37][38] The ChIP results also strongly confirmed neuron. Neruoinflammation and strengthened sEPSC both promote the progression of neuropathic pain (Figure 13).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…34,35 Furthermore, transcription factors SP1 and PU.1 have been admittedly confirmed to directly bind to glycolytic gene promoters and induce the transcription of key glycolytic enzymes to promote glycolysis. [36][37][38] The ChIP results also strongly confirmed neuron. Neruoinflammation and strengthened sEPSC both promote the progression of neuropathic pain (Figure 13).…”
Section: Discussionsupporting
confidence: 59%
“…Studies have shown that IRF5 binds to the cytokine gene promoter to enhance pattern recognition receptor‐induced cytokine expression, and IRF5 also directly binds to the bridging molecule MyD88 and the second messengers IRAK1 and TRAF6 in mouse macrophages to regulate downstream pathways 34,35 . Furthermore, transcription factors SP1 and PU.1 have been admittedly confirmed to directly bind to glycolytic gene promoters and induce the transcription of key glycolytic enzymes to promote glycolysis 36–38 . The ChIP results also strongly confirmed that IRF5 promoted the binding of SP1 and PU.1 to glycolytic gene promoters, directly suggesting that IRF5 enhanced glycolysis mainly through facilitating glycolytic gene transcription by SP1 and PU.1.…”
Section: Discussionmentioning
confidence: 67%
“…Since Sp1 is a negative prognostic factor for many tumors, it is not surprising that Sp1 regulates expression of several LncRNA, many of which are also pro-oncogenic. Table 3 summarizes a number of lncRNAs that are directly regulated by Sp1 and some of these ncRNAs are also regulated by Sp3 and Sp4 [ 86 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 ]. Sp TFs also interact with lncRNA/miRNA where there is not a direct modulation of lncRNA/Sp expression [ 144 , 145 , 146 , 147 , 148 ].…”
Section: Sp Tfs-lncrna Interactions In Cancer Cellsmentioning
confidence: 99%
“…Xia et al showed that Sp1 could promote glycolysis by activating CD147 [ 23 ]. Ning et al found that Sp1 could bind to a specific region of the SNHG22 promoter, thereby promoting glycolysis and cell proliferation in ovarian cancer cells [ 24 ]. Accumulating evidence suggests that Sp1 contributes to the regulation of mitochondrial dynamics.…”
Section: Introductionmentioning
confidence: 99%